Synthesis and Structure Determination of Substituted Thiazole Derivatives as EGFR/BRAFV600E Dual Inhibitors Endowed with Antiproliferative Activity - Lamya H. Al-Wahaibi; Essmat M. El-Sheref; Alaa A. Hassan; S. Bräse; M. Nieger; Bahaa G. M. Youssif; Mahmoud A. A. Ibrahim; Hendawy N. Tawfeek (MDPI AG, 2023)
2,3,4-trisubstituted thiazoles 3a-i, having a methyl group in position four, were synthesized by the reaction of 1,4-disubstituted thiosemicarbazides with chloroacetone in ethyl acetate/Et3N at room temperature or in ethanol under reflux. The structures of new compounds were determined using NMR spectroscopy, mass spectrometry, and elemental analyses. Moreover, the structure of compound 3a was unambiguously confirmed with X-ray analysis. The cell viability assay of 3a-i at 50 µM was greater than 87%, and none of the tested substances were cytotoxic. Compounds 3a-i demonstrated good antiproliferative activity, with GI50 values ranging from 37 to 86 nM against the four tested human cancer cell lines, compared to the reference erlotinib, which had a GI50 value of 33 nM. The most potent derivatives were found to be compounds 3a, 3c, 3d, and 3f, with GI50 values ranging from 37 nM to 54 nM. The EGFR-TK and BRAFV600E inhibitory assays' results matched the antiproliferative assay's results, with the most potent derivatives, as antiproliferative agents, also being the most potent EGFR and BRAFV600E inhibitors. The docking computations were employed to investigate the docking modes and scores of compounds 3a, 3c, 3d, and 3f toward BRAFV600E and EGFR. Docking computations demonstrated the good affinity of compound 3f against BRAFV600E and EGFR, with values of −8.7 and −8.5 kcal/mol, respectively.